The exclusion of Russia from Council of Europe: initial reflections on the effects (Ius Novum, 2024)
The new situation related to Russia’s aggression against Ukraine led to Russia’s exclusion from the Council of Europe and then European regional human rights protection system in March 2022. This article aims to examine the legal and political consequences of the Russian Federation’s exclusion from the Council of Europe and the European human rights protection system. The research objective was achieved through the analysis of normative acts (hard law, soft law) of the Council, a review of domestic and foreign literature, and the analysis of statistical data provided by the Council and the European Court of Human Rights. The article seeks to answer the following research questions: 1. What are the actual and potential consequences of excluding Russia from the Council for both Russia and other member states?, 2. What impact will Russia’s exclusion from the Council of Europe and the European human rights protection system have on the citizens of Russia and those under its jurisdiction? Membership in the Council of Europe entails mandatory participation in the European human rights protection system, based on the European Convention on Human Rights and the European Court of Human Rights. The primary consequences of Russia’s exclusion from the Council are: 1. exclusion from the family of European states, 2. denunciation of the Convention and other agreements adopted within the organisation, and 3. the inability to file individual and interstate complaints against Russia.
Keywords: Council of Europe, Russia, human rights